Marizomib irreversibly inhibits proteasome to overcome compensatory hyperactivation in multiple myeloma and solid tumour patients. (9th May 2016) - Levin, Nancy; Spencer, Andrew; Harrison, Simon J.; Chauhan, Dharminder; Burrows, Francis J.; Anderson, Kenneth C.; Reich, Steven D.; Richardson, Paul G.; Trikha, Mohit
Summary: Proteasome inhibitors (PIs) are highly active in multiple myeloma (MM) but resistance is commonly observed. All clinical stage PIs effectively inhibit chymotrypsin‐like (CT‐L) activity; one possible mechanism of resistance is compensatory hyperactivation of caspase‐like (C‐L) and trypsin‐like (T‐L) subunits, in response to CT‐L blockade. Marizomib (MRZ), an irreversible PI that potently inhibits all three 20S proteasome subunits with a specificity distinct from other PIs, is currently in development for treatment of MM and malignant glioma. The pan‐proteasome pharmacodynamic activity in packed whole blood and peripheral blood mononuclear cells was measured in two studies in patients with advanced solid tumours and haematological malignancies. Functional inhibition of all proteasome subunits was achieved with once‐ or twice‐weekly MRZ dosing; 100% inhibition of CT‐L was frequently achieved within one cycle at therapeutic doses. Concomitantly, C‐L and T‐L activities were either unaffected or increased, suggesting compensatory hyperactivation of these subunits. Importantly, this response was overcome by continued administration of MRZ, with robust inhibition of T‐L and C‐L (up to 80% and 50%, respectively) by the end of Cycle 2 and maintained thereafter. This enhanced proteasome inhibition was independent of tumour type and may underlie the clinical activity of MRZ in patients resistant to other PIs.